The Role of the Ceo's Educational Background on the Relationship Between Intellectual Capital and Performance Among Indonesian Listed Banks - Samantha Agnesia Lidya Br. Gultom; Arief Wibisono Lubis (Syntax Corporation, 2023)
The transition from a physical resource-based economy to a knowledge-based economy has encouraged researchers to look for new ways to measure intangible assets such as intellectual capital. This study tests and analyzes the effect of intellectual capital on company performance and the role of educational background in the influence of intellectual capital on the performance of banking companies listed on the Indonesian stock exchange for the period 2018-2022. This study uses secondary data obtained from the official website of the sample company. The number of samples in this study was 47 banks listed on the Indonesian Stock Exchange (IDX). The value-added intellectual coefficient (VAIC) method was used to measure the added value of intellectual capital. This study uses quantitative methods with panel data regression to analyze the effect of intellectual capital on company performance and the effect of managing directors’ educational background on the relationship between intellectual capital and company performance. These findings show how IC elements of intellectual capital affect financial performance. We discover that IC improves the ROA and ROE of Banking Companies Listed in Indonesia, data analysis results indicate that the educational background of the managing director has a varying impact on the relationship between intellectual capital (IC) and company performance, as measured by return on assets (ROA) but not to return on equity (ROE). To the best of the author’s knowledge. This is the first empirical study to evaluate the Role of a CEO's educational background in affecting Intellectual Capital in the performance of banking companies listed in Indonesia.